Qualifying the difficulty of embryo transfer with a visual analogue scale and assessing its impact on IVF outcomes. (3rd July 2019) - Coats, Edward; Carden, Hannah; Zujovic, Lyndsey; Maalouf, Walid; Hopkisson, James; Raine-Fenning, Nicholas
Abstract: The aim of this study was to determine whether a continuous visual analogue scale (VAS) is a reliable tool to grade embryo transfer (ET) difficulty when assessing IVF outcomes. No standardized grading system exists for reporting ET 'difficulty' which is typically recorded in descriptive terms. Clinicians performing 188 fresh single ETs between November 2014 and May 2016 also recorded a VAS score (0–100). Embryo transfers were stratified into three levels of ET 'difficulty': (A) 'easy' – no resistance; (B) 'medium' – resistance overcome by advancing the catheter's outer sheath; and (C) 'difficult' – a malleable stylet was required to overcome resistance; and these compared to the VAS scores. Clinical pregnancy and live birth rates were the primary outcomes. VAS scores were categorized into four incremental groupings according to the 25th, 50th and 75th percentiles (Groups 1–4) for analysis. No significant relationship ( p > 0.05) was seen in clinical pregnancy or live birth rates in either the standard difficulty or the VAS groupings. The median VAS scores in Groups A–C increased as difficulty increased, but the interquartile ranges overlap with wide clinician variation, suggesting the VAS is not itself a reliable enough tool to record ET difficulty in isolation.